(untitled) (Global Journal of Human-Social Science, 2025)
Hiding treasures sacred objects and precious documents belonging to temples or religious communities in some secret hiding places was common practice in ancient Palestine During Judas s kings time the priests of Jerusalem s Temple also followed this practice Tradition exists about a crypt where just before Nebuchadnezzar destroyed the Temple several objects of the cult were hidden and among them the ark of the covenant These traditions have given rise to extensive research and diggings on the Temple Mount since the times of the Templars A vast amount of literature exists on the subject which is not worth mentioning as it relates to traditions of unknown origin and trustworthiness of little use in establishing the truth It would be different if we could find precise references to this hiding place in the Bible itself or some independent and equally ancient sources This expectation however looks na ve The primary prerogative of a secret is that of being kept secret It is obvious that their actual owners avoided talking about it and controlled as far as they could the media of their time trying to prevent the news about its existence from becoming public Surprisingly however there is a host of direct references about such a hiding place in the Bible itself which is a product of that same caste of priests who were the owners of the secret sometimes coarsely disguised by evident corruptions but in the whole quite clear and reliable The references are precise and reliable also in non-canonic and apocryphal books They provide a large amount of coherent information that cannot be discarded